Role of spiritual and psychological capital in predicting the quality of life of divorced women - Kalantari, Masoumeh; Sotoudeh, Samaneh; Dehghan Banadaki, Maryam; Arbakri, Fatemeh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of the present study was to predict the quality of life of divorced women based on spiritual and psychological capital. Method: The research population included all women referring to the Kosar Charity Institute in Karaj, of which 260 were selected by targeted sampling and then by the World Health Organization Quality Questionnaire (WHOQOL), GolParvar Spiritual Capital Questionnaire and Luthans Psychological Capital Questionnaires (PCQ) were evaluated. Pearson correlation coefficient and regression analysis were used to analyze the data. Results: The results showed that spiritual capital and psychological capital can explain 22.9 % of the quality-of-life quality in divorced women and between spiritual capital (β = 0.221) and psychological capital (β = 0.329) and quality of life. There is meaningful (P <0.1) such psychological capital had the highest share in predicting the quality of life of divorced women. Conclusion: Based on the results, it can be stated that spiritual and psychological capital play a role in predicting the quality of life of divorced women.